Mapping Intercultural Communication Imperatives of Police-Public Interactions in Rural Spaces - Ndhlovu, Finex; Mulrooney, Kyle; Mutongwizo, Tariro; Harkness, Alistair (International Journal of Rural Criminology, 2022)
This research note seeks to generate fruitful pathways to advance a new discourse on intercultural encounters between the police and individuals from multilingual communities in Australia’s increasingly diverse rural and regional settings. How might police officers better relate and communicate with groups of migrants whose language practices are complex, unpredictable and eschew the widely used logics of translation and interpretation? How might we encourage hope in our social communities that intercultural understanding between policing agencies and new migrants is key to co-creating peaceful and resilient rural communities? How might police communication protocols that assist in supporting the retention of migrants’ linguistic capabilities and funds of knowledges contribute to the wellbeing of regional communities? What would policing rural and regional communities look like if we were to centre sociolinguistic and intercultural imperatives? In this research note, we consider these questions in our search for the next steps in mapping police communication protocols that work for all in Australia’s rural and regional settings. The goal is to contribute new conceptual approaches we can use to foster partnerships and trusting relationships between the police and our increasingly diverse rural populations.